Рroblems of modeling of the physical education pupil and student youth. - Vovk V. M. (Kharkov National Pedagogical University, 2010)
The modern methodological approaches are сonsidered in modeling of the process of the physical education. The broughted analysis publication about modeling of the physical education in average and high school. Contextual education and physical education are a practical realization competencical approach and principle to receivership of the physical education pupils and students. It is proved that introduction base and perspective models in practical of the work, raises efficiency of the physical education. It is installed that in physical education necessary organic combination tradition and innovation.